EXUTÓRIOS NATURAIS DO SISTEMA EXU/ARAJARA NA BACIA DO ARARIPE - MONTALVERNE, ALARICO ANTONIO FROTA; DA COSTA, WALDIR DUARTE; JUNIOR, ANTONIO HONORIO DE MELO; FILHO, JOSÉ AUGUSTO VIEIRA; PONTES, JOÃO SÉRGIO AMARAL; LOPES, CARLOS FERNANDES; DA SILVA, EMANUEL CARLOS CEZÁRIO (Águas Subterrâneas, 1994)
RESUMO NÃO DISPONÍVEL